Investigating stereotypes about the target language country: A case of German language learners - Nikitina, L.; Mohd Don, Z.; Loh, S.C. (2014)
Language learners bring into the classroom a multitude of stereotypes about the target language country, culture and native speakers. Recognizing an important role that these images play in the process of learning a foreign language, several research studies have explored stereotypes held by language learners. For the most part, these studies were qualitative in nature and they mainly focused on the stereotype content. There is also a lack of studies that examine frequency and salience of the stereotypical images about Germany held by the learners of German. The current mixed methods study addresses these gaps. It extends research on stereotypes in the field of applied linguistics by qualitatively exploring the content and quantitatively assessing favourability and salience of the language learners’ stereotypical images. This study was conducted among beginner learners of German in a big public university in Malaysia. The findings revealed that the students’ stereotypes about Germany included references to sport, science, technology, industry, culture, history, people, language, geography and food. The most salient stereotypes were “football”, “cars”, “technology”, “engineering”, “Volkswagen” and “big industries.” For the most part, the stereotypes about Germany held by the students were positive.